Paroxysmal generalized dystonia with clinical fluctuation affected by the menstrual cycle. (June 2020) - Jo, Sungyang; Park, Kye Won; Choi, Nari; Ryu, Ho-Sung; Kim, KiJu; Kim, Young Jin; Chung, Sun Ju
Highlights: A patient with ATP1A3 mutation can present with paroxysmal generalized dystonia without hemiplegic event. Menstrual cycle could be a precipitating factor of paroxysmal movement disorder in patients with ATP1A3 mutation. Progesterone, which peaks during the mid-luteal phase might have an inhibitory effect on Na+/K+ ATPase activity.